New insight into the systematics of Tomoceridae (Hexapoda, Collembola) by integrating molecular and morphological evidence. (29th November 2015) - Yu, Daoyuan; Zhang, Feng; Stevens, Mark I.; Yan, Qibao; Liu, Manqiang; Hu, Feng
Abstract : Tomoceridae is common but among the most problematic groups of Collembola. Its position within Collembola and the relationships within the family remain obscure. This also extends to the generic division of the subfamily Tomocerinae that remains controversial. This study examines these issues by integrating both molecular and morphological evidence. Our molecular phylogeny based on rDNA sequences supports the monophyly of Tomoceridae and the sister relationship between Tomocerinae and Lepidophorellinae. Reconstructions and tree topology tests constraining monophyly did not resolve the relationships between Tomoceridae and other collembolan groups. We also examined the morphology of the first instar (primary) larvae, which has significant phylogenetic value among higher Collembola. Mapping primary chaetotaxy onto our molecular phylogeny provided further evidence for the unique position of Tomoceridae within Entomobryomorpha and Collembola. The monophyly and subfamilial classification within Tomoceridae were validated here, whereas its position among Collembola will need further studies in a broader consideration across the major collembolan orders. Within Tomocerinae, the monophyly of Pogonognathellus was demonstrated, but the status of Tomocerus and Tomocerina is still to be resolved.